Ubiquitin and Autophagy - Nazarko, Taras Y. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book is a collection of articles from the Cells Special Issue on "Ubiquitin and Autophagy". It contains an Editorial and 13 articles at the intersection of ubiquitin- and autophagy-related processes. Ubiquitin is a small protein modifier that is widely used to tag proteins, organelles, and pathogens for their degradation by the ubiquitin-proteasome system and/or autophagy-lysosomal pathway. Interestingly, several ubiquitin-like proteins are at a core of the autophagy mechanism. This book dedicates a lot of attention to the crosstalk between the ubiquitin-proteasome system and autophagy and serves as a good starting point for the readers interested in the current state of the knowledge on ubiquitin and autophagy.